Mycobacteria manipulation of host proteases and inflammatory pathways during infection within human macrophages and dendritic cells - Marques, Joana Pereira, 1989- (2014)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2013